2021
DOI: 10.1108/jopp-07-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Significant governance factors in PPP infrastructure delivery performance in Ghana

Abstract: Purpose Inefficiencies in public-private partnership (PPP) has been attributed to deficient and poor governance practices and structures. It has been recognized that a veritable way to achieve efficiency in PPP governance is through gaining an understanding of the theoretical, practical and contextual factors that underline governance practices in PPP project delivery. The purpose of this study is to explore the significant governance factors in PPP project performance and delivery. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Additionally, close collaboration between public and private parties can ensure continuous and effective communication between the two parties during the operation of a PPP project. Communication can improve the understanding between partners (Hu et al, 2021) and contribute to sustainable project performance by sharing project-related information (Kwofie et al, 2021).…”
Section: Results Of Mediation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, close collaboration between public and private parties can ensure continuous and effective communication between the two parties during the operation of a PPP project. Communication can improve the understanding between partners (Hu et al, 2021) and contribute to sustainable project performance by sharing project-related information (Kwofie et al, 2021).…”
Section: Results Of Mediation Analysismentioning
confidence: 99%
“…Communication can improve the understanding between partners (Hu et al. , 2021) and contribute to sustainable project performance by sharing project-related information (Kwofie et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These included heads of procurement units, project managers, heads of user departments, accounting officers, heads of finance units, project consultants, chairmen of the tender boards and auditors. Participants were chosen based on their rational roles in planning, execution and overseeing compliance with PGG in public construction projects (Kwofie et al, 2021;Matto et al, 2021). The basis for selecting the 24 PEs is that they were identified by the Controller Auditor General (CAG) as having implemented construction projects with indicators suggesting the likelihood of achieving VfM, such as cost-effectiveness, timely delivery and quality standards (URT, 2021).…”
Section: Research Design and Samplingmentioning
confidence: 99%
“…This issue is particularly pronounced in Sub-Saharan Africa, where 80% of construction projects fail to achieve VfM, encountering delays and cost overruns (World Bank, 2020). Studies conducted by Idrees and Shafiq (2021), Israel (2022) and Kwofie et al (2021) revealed corrupt practices as the main obstacle hindering PEs from realising VfM in public construction projects. This results in PEs losing approximately 20% to 30% of the project value (World Bank, 2020).…”
Section: Introductionmentioning
confidence: 99%